Pengaruh Perlindungan Konsumen, Kepatuhan Pajak, dan Deteksi Fraud terhadap Kinerja UMKM Batik Kota Pekalongan - Hakim, Mujibul; Miyasari, Fangela; Dwirainaningsih, Yustiana; Syaqiq, Muhammad (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research aims to examine the influence of consumer protection, tax compliance and fraud detection on the performance of batik Micro, Small and Medium Enterprises (MSMEs) in Pekalongan City. MSMEs are the backbone of the Indonesian economy, with batik as a cultural heritage recognized by UNESCO, providing opportunities to improve national economic performance. This research uses a quantitative approach with a sample of 155 respondents from a total population of 1645. Data was collected through a questionnaire that measured the variables of consumer protection, tax compliance and fraud detection, as well as the performance of MSMEs. By using regression analysis via the SPSS application, the results show that the three independent variables have a significant effect on the performance of batik MSMEs. These findings emphasize the importance of consumer protection, compliance in tax payments, and fraud detection to improve the performance of MSMEs. It is recommended that batik MSMEs in Pekalongan improve services to consumers, comply with taxes, and understand the characteristics of fraud to strengthen the performance of batik MSMEs in Pekalongan.